Unexpected Complication of Hydroxocobalamin Administration for Refractory Vasoplegia in Orthotopic Liver Transplant: A Case Report. (December 2019) - Crouch, Cara; Hendrickse, Adrian; Gilliland, Samuel; Mandell, M. Susan
A 40-year-old male with alcoholic cirrhosis and end-stage renal disease presented for simultaneous liver and kidney transplantation. Hemodialysis was utilized intraoperatively during liver transplantation. During the procedure, the patient developed refractory hypotension and ultimately received hydroxocobalamin for vasoplegia. Shortly after administration, the hemodialysis machine ceased working after a "blood leak" alarm developed. Without the ability to continue intraoperative dialysis, the kidney transplantation portion of his surgery was postponed. The patient was transferred to the intensive care unit, where he underwent continuous renal replacement therapy overnight, and his kidney transplant proceeded the following morning.